Cultivation of Top Innovative Talents Leads the Formation of New Quality Productivity: Ideal Picture, Realistic Dilemma and Practical Way Forward - Tang, Miaomiao; Sun, Li; Zeng, Zhen (Journal of Research in Vocational Education, 2024)
Top-tier innovative talents possess characteristics of innovation, leadership, sociality, timeliness, and openness, which meet the needs of the development of new quality productivity. Vigorously cultivating top-tier innovative talents is a key factor in leading the formation of new quality productivity. The cultivation of top-tier innovative talents generates the connotation of new quality productivity, and the formation of new quality productivity also influences the training concepts and quality structure of top-tier innovative talents. There is an inherent logic of two-way drive and mutual promotion between the two. With the acceleration of the current new round of scientific and technological revolution and industrial transformation, the cultivation of top-tier innovative talents leading to the formation of new quality productivity faces practical dilemmas such as the lack of future-oriented thinking in talent cultivation, insufficient coordination in the talent cultivation system, and a lack of diversity in the types of talent cultivation. It is necessary to take a holistic approach, focusing on integrating educational resources, incubating cross-border innovation, advancing human-machine cooperation, adhering to open training, and highlighting regional characteristics to continuously exert efforts, explore new paths for the cultivation of top-tier innovative talents, and lay a talent foundation for accelerating the formation of new quality productivity. aggressive behavior in older preschoolers has long been a nuisance to kindergarten teachers and parents, and it is a common yet difficult problem in society. This study recorded the proportion, context, and reasons for aggressive behavior in older preschoolers at the Tianfu New Area Experimental Kindergarten in Chengdu. Combining the physical and mental development patterns of older preschoolers, methods such as observation records and situational analysis were used. Through real confrontation, observation, analysis, and exploration, effective ways to reduce and correct aggressive behavior in older preschoolers were found, with the aim of helping teachers cope with such behaviors.